Seismic characteristics of X-cable braced frames bundled with a pre-compressed spring - Mehrabi, M.H.; Ibrahim, Zainah; Ghodsi, S.S.; Suhatril, Meldi (Elsevier, 2019)
The performance of steel structures can be enhanced against lateral loads by various methods; of these, bracing systems are the most common. Past studies have shown that tension-only braced frames provide more structural stability, and hence offer better resistance when the frame is subjected to lateral loads. In a comparison between a braced and bare frame, the additional efficiency offered by the bracing depends on the selection of bracing system. This paper proposes a cable brace system with a pre-compressed spring (PCS) that bundles the wire-rope bracing members at the intersection point. Both experimental and analytical studies are conducted, and no loosening in the cable is observed, as the cables are held tension by the spring's force; thus the ability of the bracing system to cause impulses is eliminated. The final strength of the cables is reached at larger lateral displacement of the frame compared to ordinary cross cable bracing system. The equations involved in the proposed technique are discussed before being verified using finite element (FE) solutions based on ABAQUS analysis. It can be concluded that the ductility and strength of the tested specimens was significantly improved by means of the proposed technique.